Maternal Pregnancy and Pre-Pregnancy Weight and Behavioural Outcomes in Children - Berihun A. Dachew; Akilew A. Adane; Rosa Alati (Behavioral Sciences, 2024)
Reported associations of pre-pregnancy weight and/or gestational weight gain with offspring behavioural outcomes are inconsistent. Using data from the Avon Longitudinal Study of Parents and Children (ALSPAC), this study aimed to examine these associations at five developmental stages between the ages of 3 and 16. Over 6800 mother–offspring pairs at age 3 and 3925 pairs at age 16 were included. Pre-pregnancy underweight was associated with a 22% increased risk of total behavioural difficulties (OR = 1.22, 95% CI 1.02–1.45). In separate analyses using the SDQ subscales, pre-pregnancy underweight was linked to a 37% (OR = 1.37, 95% CI 1.14–1.65) and 33% (OR = 1.33, 95% CI 1.01–1.76) increased risk of emotional symptoms and prosocial behaviour problems over time, respectively. While pre-pregnancy overweight was associated with an 11% (OR = 1.11, 95% CI 1.03–1.20) and 18% (OR = 1.18, 95% CI 1.03–1.36) increased risk of conduct and peer relationship problems, respectively, pregnancy obesity was associated with a 43% increased risk of emotional problems (OR = 1.43, 95% CI 1.16–1.77). We found no evidence of associations between gestational weight gain and child behaviour except for a reduced risk in prosocial behaviour problems (OR = 0.82, 95% CI 0.70–0.96). Our findings provide insights into the link between preconception BMI and child behaviour, underscoring the necessity for further research to validate these associations and elucidate underlying mechanisms.